Home ownership is an Indians dream: A Comparative study on Impact of Demographic Factors on Home Ownership - Ch. , Hari Govinda Rao; M., Srinu; P. , Sanyasi Rao (International Journal of Psychosocial Rehabilitation, 2020)
Because of fast population development, there is a hurried amplification in the housing sector, and consequently, housing-related activities are also sensible, prompted the development of the housing finance sector in India. Consequently, a large number of private and public sector financial institutions have entered the housing sector. Though India has an enormous history of establishing housing finance institutions, there is still a need to give much attention to adopting appropriate policies & procedures to cater to housing loans. The demographic factors are the major key factors that influence the borrower’s decisions, and thus there is a need for the study and the due influence. At this juncture, this paper makes an attempt to understand the influence of demographic factors on borrowers, and there is a desperate need to understand the impact of each factor. This paper provides useful insight to explore the ground reality, which helps policymakers and encourages constructive judgment. At this juncture, the researcher has conducted a sample survey and examined the influence of socio-economic factors of respondents’ demographic factors that had influencing factors of homeownership through financial institutions. The study applied MLR (multiple linear regression) analysis of critical autonomous variables with the assistance of Z-tests and also adopted ANOVA tests to discover the degree of variety in the choices of home loan borrowers.